Investigating The Consumer Perception and Investment Pattern ‎Towards Gold Ornaments in Bengaluru City for Sustainable ‎Development - Eshwar , Lakshmi; Selvalakshmi , Dr. G. (International Journal of Accounting and Economics Studies, 2025)
This study investigates consumer perception and investment patterns towards gold ornaments in Bengaluru, India, aiming to identify ‎important aspects influencing consumer behavior. A descriptive research design was adopted, with data collected from 481 respondents ‎through structured questionnaires. Findings reveal a higher representation of female respondents, primarily aged between 30 to 50 years old, ‎and predominantly employed in the private sector. Multivariate tests indicate significant effects of gender, age, and occupation on consumer ‎perception and investment behavior towards gold ornaments. Specifically, gender significantly influences perceptions of prestige, design ‎importance, investment safety, and price influence. Age demonstrates significant effects on selected perceptions and behaviors. Additionally, ‎occupation plays a notable role, particularly in perceptions related to prestige and investment safety. The study highlights the significant ‎influence of the price of gold on investment decisions and the perception of gold ornaments as symbols of wealth preservation and social ‎status. Females are more likely purchasers than males, as both sexes should see gold ornaments as objects for personal adornment and ‎investment. Respondents find purchasing from jewelry stores the best choice, as they are aware that the jewelry will have been invested in. Finally, ‎the study showed that occupation does not play a big role in predicting how reliable gold ornaments will be perceived by people. ‎However, the results highlight the intricate relationship between demographic factors and consumers’ perceptions and behaviors when it ‎comes to gold ornaments in Bengaluru city‎.